Nutrient Management for Improving Mungbean [Vigna radiata (L.) Wilczek] Productivity in Acidic Soil of Northeast India - SINGH, A.K.; SINGH, P.K.; KUMAR, MANOJ; BORDOLOI, L.J.; JHA, A.K. (Indian Journal of Hill Farming, 2015)
A field experiment was carried out to study the effect of sulphur (S) and cobalt (Co) fertilization in combinations with Rhizobium inoculant (RI) and recommended NPK fertilization (RDF) on growth, yield and nutrient uptake of mungbean in an acidic soil of northeast India. Application of RI alone or in combination with S or Co (without NPK) could not significantly increase the grain yield, but combined application of RI+S+Co did increase it up to 450 kg ha-1from 240 kg ha-1 at control. Noticeably, application of recommended NPK (without any other inorganic or organic inputs) led to a better grain yield (530 kg ha-1), which was more than twice the yield at control. And further addition of RI+ S+ Co along with NPK (RDF) nearly tripled the yield (730 kg ha-1) compared to that of control. Effect of RI, S and Co application on crop yield was mediated mostly through increased nodulation and nutrient uptake, which were correlated well with seed yield.